Keanekaragaman Plankton Di Kolam Pertumbuhan Ikan Bandeng (Chanos chanos Forsskal) Yang Terparasiti Di Desa Balongpanggang Gresik - Rizki Kusuma Hantika; Ratna Djuniwati Lisminingsih; Nour Athiroh AS (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2020)
The role of plankton in ecology as a parameter of lush or not a waters, because plankton is the basis of the natural feed chain in the waters. The previous research has been done on the morphology and anatomy of milkfish (Chanos chanos Forsskal) at the pond in the village of Balongpanggang, Gresik, where the waters are polluted. Parasitic worms found nematodes in fish intestines have an impact on losses for fish farmers. The purpose of this study is to identify, find out the differences, determine the level of risk of the type of plankton and determine the condition of abiotic factors in the pond. The study used 24 samples from 3 parasites and 1 non-parasite pond using the Randomized Block Design (RBD) method. Based on the results of observations and identification of plankton in the Integrated Milkfish Growth Pool, there were 53 cells of Chlorococcum humicola and 37 individuals of Stentor roeseli. Phytoplankton found in all ponds, namely Chlorella variegatus, Chlorococcum humicola, Navicula cuspidata, Navicula placentula, Nostoc sphaericum, and Protococcus viridis. While Zooplankton is only 1 in all pools, namely Stentor roeseli. Unparasitic ponds have the highest plankton diversity level (5.7), rather than parasitic ponds 2 (5.0). The condition of abiotic factors (pH) in all ponds is still in accordance with water quality standards for aquaculture ponds. Keywords: Plankton, Identification, Diversity level ABSTRAK Peranan plankton dalam ekologi sebagai parameter subur tidaknya perairan, karena plankton merupakan dasar mata rantai pakan alami di perairan Penelitian terdahulu dilakukan pada morfologi dan anatomi ikan Bandeng (Chanos chanos Forsskal) dalam suatu tambak di desa Balongpanggang, Gresik yang perairannya tercemar. Ditemukan cacing parasit nematoda dalam usus ikan yang berimbas pada kerugian bagi petani ikan. Tujuan dari penelitian ini yaitu untuk mengidentifikasi, mengetahui perbedaan, tingkat kenekargaman jenis plankton dan kondisi faktor abiotik kolam. Penelitian menggunakan 24 sampel dari 3 kolam yang terparasiti dan 1 kolam yang tidak terparasiti dengan metode Rancangan Acak Kelompok (RAK). Berdasarkan hasil pengamatan dan identifikasi plankton pada Kolam Pertumbuhan Ikan Bandeng yang Terparasiti didapatkan spesies Chlorococcum humicola sebanyak 53 sel dan spesies Stentor roeseli sebanyak 37 individu. Ditemukan Fitoplankton yang keberadaannya ada di semua kolam, yaitu Chlorella variegatus, Chlorococcum humicola, Navicula cuspidata, Navicula placentula, Nostoc sphaericum, dan Protococcus viridis. Sedangkan Zooplankton hanya 1 disemua kolam, yaitu Stentor roeseli. Kolam tidak terparasiti merupakan kolam yang memiliki nilai tingkat keanekaragaman plankton tertinggi (5,7), daripada kolam terparasiti 2 (5,0). Kondisi faktor abiotik (pH) pada semua kolam masih sesuai standar kualitas air untuk budidaya tambak. Kata kunci: Plankton, Identifikasi, Indeks Keanekaragaman